2011
DOI: 10.1091/mbc.e11-04-0343
|View full text |Cite
|
Sign up to set email alerts
|

Functional ESCRT machinery is required for constitutive recycling of claudin-1 and maintenance of polarity in vertebrate epithelial cells

Abstract: Drosophila ESCRT mutants lose epithelial polarity and show increased proliferation, suggesting that ESCRT proteins act as tumor suppressors. In this study, we show for the first time to our knowledge that ESCRT proteins are required to maintain polarity in mammalian epithelial cells, supporting the idea that ESCRT proteins are tumor suppressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 79 publications
3
85
1
Order By: Relevance
“…PKC and PKA activity were shown to modulate claudin1 expression and intracellular localization, respectively (42,44,45). Endocytic recycling is also known to regulate internalization of TJ proteins (64). Our present study uncovers a functional role for NF-Bp65 in transcriptional regulation of claudin1 gene.…”
Section: Discussionsupporting
confidence: 53%
“…PKC and PKA activity were shown to modulate claudin1 expression and intracellular localization, respectively (42,44,45). Endocytic recycling is also known to regulate internalization of TJ proteins (64). Our present study uncovers a functional role for NF-Bp65 in transcriptional regulation of claudin1 gene.…”
Section: Discussionsupporting
confidence: 53%
“…ZO-1 and occludin) rapidly exchange between TJ and extra-junctional pools, whereas others (e.g. claudins) do not (42). Recent studies demonstrated that, at least in some cells, claudins (including claudin-1) are continuously removed from cell surfaces via an endosomal sorting complex required for a transport-dependent process after ubiquitination by LNX1p80 (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…claudins) do not (42). Recent studies demonstrated that, at least in some cells, claudins (including claudin-1) are continuously removed from cell surfaces via an endosomal sorting complex required for a transport-dependent process after ubiquitination by LNX1p80 (42,43). Internalization into endosomes can lead to recycling to cell surfaces or ultimately to lysosomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, loss of Rab5 or endosomal sorting complex required for transport (ESCRT) components results in disorganized overgrowth of imaginal epithelia, whereas mutations that disrupt subsequent stages of endocytic trafficking do not. Rab5 and ESCRT also regulate apical polarity in mammalian epithelia (Dukes et al, 2011;Zeigerer et al, 2012), while Par mutations in several systems can cause defects in cargo internalization and endolysosomal traffic (reviewed by Shivas et al, 2010). Here we investigate the hypothesis that Scrib mediates polarity through influencing endocytic itineraries.…”
Section: Introductionmentioning
confidence: 99%